The regulatory role of job satisfaction in the effect of fear of disease contagion/transmission on food hygiene attitude in cafe workers. - Çelebi, İsmet; Çalışkan, Cüneyt (Work, 2026)
Background: A lack of attention to hand and food hygiene may result in food workers to absent themselves from their duties. In such a case, the probability of an outbreak can be mitigated by halting the contact of infected individuals with foodstuffs during the food processing phase. Objective: The objective of this study was to examine the regulatory role of job satisfaction in the effect of fear of disease transmission on hand and food hygiene attitudes among café workers. Methods: The study sample comprises 677 café employees. The data collection tools employed in the study were the Disease Contagion/Transmission Scale, the Hand and Food Hygiene Attitude Scale, and the Minnesota Job Satisfaction Scale. Hayes's (2018) Process Macro was utilized to examine the regulatory effect, and Model 1 was selected. The relationships between the measurement tools utilized in the study were interpreted with the assistance of Pearson correlation analysis. For statistical significance, p <.05 was preferred. Results: The findings indicate that job satisfaction plays a regulatory role in the effect of fear of disease contagion/transmission on hand and food hygiene attitudes. Individuals with high levels of job satisfaction and fear of disease contagion/transmission demonstrate higher hand and food hygiene attitudes. Upon analysis of the regression results, it was determined that job satisfaction has a positive and significant effect on food hygiene attitudes. Conclusions: The findings of this study indicate that enhancing job satisfaction is a key factor in fostering positive outcomes with regard to food hygiene attitudes.